TCSC Optimization for Loss Minimization in Power System Using Computational Intelligence Techniques - Balasubramaniam N.; Musirin I.; Kamari N.A.M.; Ibrahim A.A. (Springer Science and Business Media Deutschland GmbH, 2025)
Minimizing power loss in transmission systems is crucial for achieving energy efficiency, lowering temperature rise and less monetary losses leading to sustainable power system network. Flexible AC Transmission Systems (FACTs) has been vastly adopted in minimizing the power loss in power transmission systems. However, the effectiveness of FACTs devices in achieving these benefits relies heavily on their optimal placement and sizing within the transmission system. Suboptimal solutions on FACTs devices location and sizing results to under-compensation or over-compensation, both of which are undesirable outcomes. Therefore, robust optimization techniques are necessary to attain optimal solutions. This study applies evolutionary programming (EP) and artificial immune system (AIS) as the computational intelligence techniques to examine the effects of thyristor controlled static compensators (TCSC) for loss minimization in power system. This study shows that the installation of TCSC substantially minimizes the power system loss. The IEEE 30-Bus Reliability Test System (RTS) is used to validate the proposed application and compensation scheme. The application of evolutionary programming and artificial immune system techniques provides valuable insights and solutions to power loss reduction ultimately improving the performance of transmission power systems. It was discovered that both techniques are comparable in minimizing the transmission loss in the system. ? The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2024.